Utilization of spent mushroom waste and peat as soilless growing medium for Brassica oleracea var. Alboglabra - Sendi, Hatari (2014)
Peat moss (PM) is the most widely used growing substrate for the pot culture. Due to diminishing availability and increasing price of PM, researchers are looking for viable alternatives for peat as a growth media component for potted plants. A pot study was conducted with a view to investigate the possibility of using spent mushroom waste (SMW) for kailan (Brassica oleracea var. Alboglabra) production replacing PM in growth media. The treatments evaluated were 100% SMW, 100% PM, and mixtures of SMW and PM in different ratios like 1:1, 1:2 and 2:1 (v/v) with or without NPK amendment. The experiment was arranged in a completely randomized design (CRD) with five replications per treatment. Chemical properties like pH and salinity level (EC) of SMW were within the acceptable range of crop production but, nutrient content, especially nitrogen content was not enough to provide sufficient nutrition to plant for normal growth. Only PM (100%) and SMW and PM mixture in 1:2 ratio with NPK amendment performed equally in terms of kailan growth. This study confirms the feasibility of replacing PM by SMW up to maximum 50% in the growth media, and suggests NPK supplementation from inorganic sources to ensure higher productivity of kailan. Further testing was conducted to study the effects of various rates of SMW with virgin peat (VP) and non-virgin peat (NVP) at different location on the growth and yield of kailan. The peat sampling for VP and NVP was collected at Malaysian Agricultural Research and Development Institute (MARDI), Pontian Johor. The treatments evaluated were 100% SMW, 100% VP, 100% NVP and mixtures of SMW and VP or NVP in different ratios like 1:1, 1:2 and 2:1 (v/v) with NPK amendment. The experiment was arranged in a completely randomized design (CRD) with five replications per treatment. Result was obtained from peat soil in Peninsular Malaysia (Johor) indicated that no significant differences occurred between treatments that contained the portion of SMW with VP and SMW with NVP when amended with NPK. Plant height, leaf number, leaf fresh weights, leaf dry weight, total leaf area and chlorophyll content increased significantly when kailan were planted with amended NPK especially on NVP. The media with 100% NVP also showed a better plant growth because of the existing of fertilizer in the soil which is came from previous agriculture activities. For experiment three, the peat sampling was collected at Malaysian Agricultural Research and Development Institute (MARDI), Saratok Sarawak. Result obtained from observation in Sarawak also showed the media with amended NPK, fertilized soilless, there is not much differences among VP and NVP. This is due to the pH reading for all treatments gave almost similar result in between pH 3.63 to pH 5.04. Plants grown in soilless media that contained portions of SMW and NVP gave better result compared to plants grown in media that contained SMW and VP. Further studies should be conducted under various conditions with plant species or other horticultural crops. Since imported PM is expensive and not economical to use as part of the soilless media, more studies need to be done to determine the modifications on soil fertility, and fertilizer requirements should be taken into account to enable SMW and peat compound to become a soilless media.